Developing climate-smart agriculture to face climate variability in West Africa: Challenges and lessons learnt. (20th June 2018) - Partey, Samuel T.; Zougmoré, Robert B.; Ouédraogo, Mathieu; Campbell, Bruce M.
Abstract: This paper reviewed the prospects for climate-smart agriculture (CSA) development and promotion in West Africa as well as lessons learnt and challenges with a focus on climate change and variability. It was evident from the literature that West Africa is vulnerable to climate change and variability, on account of its socio-economic and physical characteristics. As climate change and variability persists, the region's quest to use agriculture as the mainstream opportunity to deliver on set targets of the sustainable development goals will be strongly challenged without appropriate interventions. Adopting CSA seems to be a suitable strategy to achieving food security while also mitigating and adapting to climate-related risks. Among numerous CSA technologies, the review found (1) agroforestry (farmer-managed natural regenerations), soil and water conservation technologies (zai, half-moon, tie/contour ridges, conservation agriculture) and (3) climate information services as highly valued promising options for climate change adaptation and risk management in West Africa. In addition, institutional settings at the community, national and regional levels such as the establishment of multi-stakeholder innovation platforms, national science policy dialogue platforms on CSA in parts of West Africa and the formulation of the West Africa CSA Alliance were found to be crucial in promoting capacity development and awareness of CSA technologies and innovations in the region. The review found that CSA still faces a number of challenges, including: lack of clear conceptual understanding, limited enabling policy and financing. The prospects of CSA in West Africa hinge on the capacities of farming households and the region's national institutions to understand the environmental, economic and social challenges in the context of climate change, and consequently self-mobilize to develop and implement responsive policies at appropriate scales.